2021
DOI: 10.3390/ijms22168863
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Oxidative and Endoplasmic Reticulum Stress in RDH12-Related Retinopathies

Abstract: Retinol dehydrogenase 12 (RDH12) is expressed in photoreceptor inner segments and catalyses the reduction of all-trans retinal (atRAL) to all-trans retinol (atROL), as part of the visual cycle. Mutations in RDH12 are primarily associated with autosomal recessive Leber congenital amaurosis. To further our understanding of the disease mechanisms, HEK-293 cell lines expressing wildtype (WT) and mutant RDH12 were created. The WT cells afforded protection from atRAL-induced toxicity and oxidative stress. Mutant RDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Retinal histologic study of Rdh12 −/− animal models has shown shortened photoreceptors that have a reduced capacity for retinoid processing, 37 , 38 and enlarged phagosomes in the RPE. 39 The latter has been associated with suboptimal RPE phagocytosis of photoreceptor outer segments, causing toxicity and subsequent cell death. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Retinal histologic study of Rdh12 −/− animal models has shown shortened photoreceptors that have a reduced capacity for retinoid processing, 37 , 38 and enlarged phagosomes in the RPE. 39 The latter has been associated with suboptimal RPE phagocytosis of photoreceptor outer segments, causing toxicity and subsequent cell death. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…To determine the optimum dosing concentrations, cells were treated with various concentrations of NACA and taurine for 24 h and the cell viability was assessed using MTT assay. TUDCA concentration was based on a previous publication [ 12 ]. For dosing experiments, cells were plated in 6-well plates at a seeding density of 600,000 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analysed using western blot, as previously described [ 12 ], using anti-BIP (1:1000; Abcam ab21685, Cambridge, UK) overnight at 4 °C. The membrane was stripped and re-probed with anti-β-actin for 2 h at room temperature (1:5000; Sigma A2228).…”
Section: Methodsmentioning
confidence: 99%
“…also suggested that RDH12 may regulate the flow of retinoids in the eye, playing an important part against light-induced photoreceptor apoptosis during persistent illumination ( 21 ). Recently, RDH12 metabolizing all-trans retinal has likewise been found to be key in protecting cells from oxidative and endoplasmic reticulum (ER) stress ( 22 ).
Figure 1.
…”
Section: Role In Visionmentioning
confidence: 99%